I am Joseph - Cohen, Barbara; Mikolaycak, Charles (Lothrop, Lee & Shepard, 1980)
Retells the Biblical story of Joseph, from his viewpoint, relating how he was sold into slavery and became the Egyptian Pharaoh's adviser